2012
DOI: 10.1002/ceat.201100676
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Low‐Pressure Device for Production of Nanoemulsions

Abstract: A novel device is applied to produce emulsions of methyl methacrylate in water with a controllable size in the range of 30–100 nm. The process is based on the reciprocating flow of the material through an abrupt contraction which generates a strong elongational flow. This results in highly efficient dispersive mixing even at moderate pressures, thus reducing viscous dissipation and improving temperature control. The original design of the device also allows easy feeding and sampling, easy adjusting of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…In our trials, a plateau value was obtained after 329 90 cycles. Such observation was also reported bySouilem et al Souilem et al, 2012) who claimed that equilibrium is reached 331 between the forces resulting from the Laplace pressure (Eq.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…In our trials, a plateau value was obtained after 329 90 cycles. Such observation was also reported bySouilem et al Souilem et al, 2012) who claimed that equilibrium is reached 331 between the forces resulting from the Laplace pressure (Eq.…”
supporting
confidence: 68%
“…This nanoemulsification was produced by 143 means of an elongation-flow micromixer (mRMX, Fig. 1a) having a 144 restriction of 250 mm, a miniaturized version of a bigger RMX 1 145 developed by (Souilem et al, 2012). Authors have shown that due 146 to its specific design, such device promotes a predominant 147 elongational flow, which is known to be more efficient than shear and imaged by the confocal microscope Leica SP2 using a 20Â dry (Table 1).…”
mentioning
confidence: 99%
“…By using these emulsification methods, the nanodroplets can be obtained by energy transfer with the presence of surfactant whose function is to decrease the interfacial tension. Our group has recently developed a new concept of reactor/mixer (called RMX) which was successfully used to produce nanoemulsions whose size can be controlled in the range 30–100 nm . The working principle of this pneumatic apparatus is based on the reciprocating flow of a crude emulsion through an abrupt contraction which generates a strong elongational‐flow, known to be more efficient, in contrast to shear flow, to rupture dispersed phase droplets into smaller ones.…”
Section: Introductionmentioning
confidence: 99%
“…Farzi et al have shown the feasibility of nanoemulsions using such kind of mixer. Another generation of static mixers relying on the principle of elongational flow was recently designed …”
Section: Introductionmentioning
confidence: 99%